PERAN ORANG TUA SEBAGAI PENDIDIK IMAN ANAK DI TENGAH PERKEMBANGAN TEKNOLOGI DIGITAL - Wati, Oktaviantina; Dewantara, Agustinus Wisnu (CREDENDUM: Jurnal Pendidikan Agama, 2021)
This research aims to describe the role of parents in educating children’s faith and the strategies applied in addressing the challenges of digital technological advancement in the St. Gregorius community of Mater Dei Parish, Madiun. This research employs a descriptive qualitative method, with data collected through semi-structured interviews involving six parents with children aged 5–12 years. The data were analyzed thematically through data reduction, data display, and conclusion drawing. The results indicate that parents have a strong awareness of their role as primary faith educators. This role is manifested through role modeling, prayer habituation, guidance, and supervision of digital technology usage. However, parents face challenges such as gadget addiction, reduced family interaction, and disruptions in children’s spiritual life. To address these issues, parents implement strategies such as limiting technology use, monitoring, and utilizing technology as a supportive medium for faith education. In conclusion, the role of parents remains the key factor in shaping children’s faith, and digital technology can be used positively when managed wisely.